2008
DOI: 10.1159/000151602
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-9 Expression Is Inversely Correlated with Estrogen Receptor Status in Breast Cancer

Abstract: Toll-like receptor 9 (TLR9) recognizes microbial and vertebrate DNA. We previously demonstrated TLR9 expression in human breast cancer cell lines and showed that TLR9 ligands stimulate their in vitro invasion. The aim of this study was to characterize TLR9 expression in clinical breast cancer specimens. Immunohistochemical staining intensity was compared with known baseline prognostic factors and distant metastasis-free survival. TLR9 expression was detected in 98% of the tumors studied (n = 141). The mean TLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
67
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 63 publications
11
67
0
Order By: Relevance
“…Interestingly, we also found that TLR9 expression was significantly higher in ER negative breast cancer compared with ER positive one in this study, which is consistent with the report by Jukkola-Vuorinen [16]. Given that TLR9 ligation could inhibit ERα-induced transactivation by activating NF-κB of breast cancer cells [11], we speculate that TLR9 may play a role in the transformation of breast cancer from hormone-dependent to hormone-independent stage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we also found that TLR9 expression was significantly higher in ER negative breast cancer compared with ER positive one in this study, which is consistent with the report by Jukkola-Vuorinen [16]. Given that TLR9 ligation could inhibit ERα-induced transactivation by activating NF-κB of breast cancer cells [11], we speculate that TLR9 may play a role in the transformation of breast cancer from hormone-dependent to hormone-independent stage.…”
Section: Discussionsupporting
confidence: 92%
“…However, we didn't observed a statistically significant difference concerning overall survival (OS) between TLR9 positive and negative breast cancer patients, which might be correlated with the limited interval from surgery and observation end point, but we did note that the longer we follow up, the wider was the difference between the two group of patients. In a recent study about the association of TLR9 and estrogen receptor expression, Jukkola-Vuorinen reported that distant metastasis-free survival was higher in the lower TLR9-expressing part of the cohort than in the higher TLR9-expressing part of breast cancer patients, which, together with our data suggested that TLR9 may be correlated with a poor prognosis by promoting metastasis of breast cancer (16). We will continue to follow those patients and analyze prospectively the association between clinical outcome of patients and TLR9 expression.…”
Section: Discussionsupporting
confidence: 81%
“…The specificity of the antibody was confirmed by doing immunohistochemical stainings with the same protocol on paraffin-embedded human tissue sections that contained lymphocytes. As expected, intracellular TLR9 staining could be seen in lymphocytes and this staining pattern was lost when the primary antibody was omitted (44). In the breast cancer specimens, the TLR9 staining intensity of the epithelial cells was graded in three representative 10Â microscopic fields per sample using a previously published method (45)(46)(47).…”
Section: Tlr9 Immunohistochemistrymentioning
confidence: 89%
“…Sections of 4 m in thickness representing tumor, dysplastic or nonneoplastic areas were immunostained by a commercial mouse monoclonal TLR9 antibody (IMG-305A; Imgenex, San Diego, Calif., USA) with a dilution of 1: 200 [23] . CD31 staining to visualize the blood vessels was performed with a monoclonal mouse IgG1 antibody obtained from DakoCytomation (Glostrup, Denmark; M 0823, clone JC70A, using the dilution of 1: 300).…”
Section: Immunohistochemistrymentioning
confidence: 99%